2020
DOI: 10.21203/rs.3.rs-117708/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human Bone Marrow-Derived Mesenchymal Stem Cell-Secreted Exosomes Overexpressing Microrna-124-3p Inhibit DLBCL Progression By Downregulating  NFATc1

Abstract: Background: Exosomes play important roles in intercellular communication by delivering microRNAs (miRNAs) that mediate tumor initiation and development, including those in diffuse large B cell lymphoma (DLBCL). To date, however, limited studies on the inhibitory effect of exosomes derived from human bone marrow-derived mesenchymal stem cells (hBMSCs) on DLBCL progression have been reported. Therefore, this study aimed to investigate the role of hBMSC-secreted exosomes carrying microRNA-124-3p in the developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Brain endothelium cell derived (bEND.3) exosomes loaded with paclitaxel and DOX crossed the BBB and significantly reduced the GBM tumor growth which was evident by the decreased fluorescent intensity in xenotransplanted zebrafish cancer model [181][182][183][184]. Various studies [185][186][187] on human bone marrow-derived exosome (hBMSC)-containing miRNA and lncRNA have reported decrease in glioma cell proliferation, invasion, and enhanced chemosensitivity to temozolomide (TMZ). As EVs carry immunomodulatory molecules, in vivo studies confirmed that exosomes from DCs loaded with chaperone rich cell-lysates elicits a potential T cell immune response against intracranial glioma in mice [188].…”
Section: Evs In Drug Delivery Systemmentioning
confidence: 99%
“…Brain endothelium cell derived (bEND.3) exosomes loaded with paclitaxel and DOX crossed the BBB and significantly reduced the GBM tumor growth which was evident by the decreased fluorescent intensity in xenotransplanted zebrafish cancer model [181][182][183][184]. Various studies [185][186][187] on human bone marrow-derived exosome (hBMSC)-containing miRNA and lncRNA have reported decrease in glioma cell proliferation, invasion, and enhanced chemosensitivity to temozolomide (TMZ). As EVs carry immunomodulatory molecules, in vivo studies confirmed that exosomes from DCs loaded with chaperone rich cell-lysates elicits a potential T cell immune response against intracranial glioma in mice [188].…”
Section: Evs In Drug Delivery Systemmentioning
confidence: 99%